Genomic analysis of Ralstonia pickettii reveals the genetic features for potential pathogenicity and adaptive evolution in drinking water - Yuan, Chao; An, Tianfeng; Li, Xinlong; Zou, Jiao; Lin, Zhan; Gu, Jiale; Hu, Ruixia; Fang, Zhongze (Frontiers in Microbiology, 2024)
Ralstonia pickettii, the most critical clinical pathogen of genus Ralstonia, has been identified as a causative agent of numerous harmful infections. Additionally, Ralstonia pickettii demonstrates adaptability to extreme environmental conditions, such as those found in drinking water. In this study, we conducted a comprehensive genomic analysis to investigate the genomic characteristics related to potential pathogenicity and adaptive evolution in drinking water environments of Ralstonia pickettii. Through phylogenetic analysis and population genetic analysis, we divided Ralstonia pickettii into 5 Groups, two of which were associated with drinking water environments. The open pan-genome with a large and flexible gene repertoire indicated a high genetic plasticity. Significant differences in functional enrichment were observed between the core and pan-genome of different Groups. Diverse mobile genetic elements (MGEs), extensive genomic rearrangements, and horizontal gene transfer (HGT) events played a crucial role in generating genetic diversity. In drinking water environments, Ralstonia pickettii exhibited strong adaptability, and the acquisition of specific adaptive genes was potentially facilitated by genomic Islands (GIs) and HGT. Furthermore, environmental pressures drove the adaptive evolution of Ralstonia pickettii, leading to the accumulation of unique mutations in key genes. These mutations may have a significant impact on various physiological functions, particularly carbon metabolism and energy metabolism. The presence of virulence-related elements associated with macromolecular secretion systems, virulence factors, and antimicrobial resistance indicated the potential pathogenicity of Ralstonia pickettii, making it capable of causing multiple nosocomial infections. This study provides comprehensive insights into the potential pathogenicity and adaptive evolution of Ralstonia pickettii in drinking water environments from a genomic perspective.